Effect of pH and ionic strength on membrane flux in the separation of escherichia coli by using cross-flow microfiltration - Ab Aziz, Nadira (2010)
Recently, cross-flow microfiltration has been used to separate cells in continuous fermentation processes. The main objective of this study is to investigate the effect of pH and ionic strength on membrane flux during the separation of Escherichia coli. In order to achieve the objective of the study, hollow fibre membrane with molecular pore size of 0.2µm and surface area of 110 cm2 was used as the filter media. The experiment was carried out at a constant transmembrane pressure of 0.8 bar by varying five different pH values, ranging from pH 4.5 to 8.5 and five different concentration of salt, ranging from 0.1M to 0.5M. From this study, it is found that pH 6.5 with low concentration of salt was the best condition for the separation of E.coli. Increasing in pH increased the permeate flux, while high concentration of salt decreased the permeate flux. As a conclusion, the membrane used in this experiment can be used in the fermentation of E.coli for cell recycling because pH 6.5 is the optimum condition for fermentation of E.coli in its fermentation broth.